PENGARUH KUALITAS PELAYANAN DAN KUALITAS PRODUK TERHADAP KINERJA PERUSAHAAN DI LARISSA AESTHETIC CENTER DENPASAR - Vidananda, Ni Ketut Pega; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 10 No 4 (2021)DO - 10.24843/EJMUNUD.2021.v10.i04.p02, 2021)
This research aimed to determine the effect of service quality and product quality on firm performance. This research was done on customers of Larissa Aesthetic Center Denpasar, which is an aesthetic clinic in Bali. The sample’s used were 100 respondents that was chosen by purposive sampling method. Data collection is done by using questioners. The technique for analyzing the data is multiple regression with SPSS. The research’s result indicated that service quality has positive and significant effect on business performance and product quality has positive and significant effect on business performance. Based on the results, hopefully the management could pay more attentions to the operational activities through the contribution of each employees in order to give a good service and pay more attention to the content and composition of product’s raw materials, as well as the accuracy of product application during the treatment process to the customers, so that the customers will more satisfy and the business performance assessment could be even better. Keywords : service quality; product quality; firm performance